LACHMAN, Gary, Jung, o místico, São Paulo: Cultrix, 2010, 1ª reimpressão, 2015, 280 p., ISBN 150.1954092 - Berni, Luiz Eduardo Valiengo (Revista Relegens Thréskeia, 2017)
Resenha do livro "Jung, o místico" de Gary Lachman. São Paulo: Cultrix, 2010, 1ª reimpressão, 2015, 280 p., ISBN 150.1954092